ANALISIS FAKTOR-FAKTOR PENYEBAB KESULITAN BERBAHASA PADA SISWA SD KELAS PEMULAAN MENURUT TEORI - Audy Mita Amelina; Femi Br Ginting; Ulpi Romadhona Nurdanti; Dr. Drs. Eko Kuntarto, M. Pd. M.Comp.Eng; Muhammad Sholeh, S.Pd., M.Pd. (STKIP Subang, 2024)
This study aims to analyze the factors that cause language difficulties in primary school students in the early grades. Language difficulties are one of the significant obstacles in the learning process and academic development of students. Through a qualitative approach with a literature study method, this research examines various theories and recent research results on language difficulties in elementary school-age children. The results show that there are four main factors that cause language difficulties: neurological factors, environmental factors, psychological factors, and pedagogical factors. Understanding these factors is important for developing effective intervention strategies to address language difficulties in early grade students. The findings are expected to guide educators and educational practitioners in creating a learning environment that supports the development of students' language skills. Keywords: language difficulties, primary school students, early grades, language development